Water Quality And Community Macroalgae In Jikumerasa Coastal Waters, Buru Island - Hairati Arfah; Simon I Patty (Jurnal Ilmiah PLATAX, 2016)
ABSTRACT The study of water quality and macroalgae community in Jikumerasa coast, Buru Island, Maluku, was conducted in June 2014. This study aims to determine the water quality in terms of physico-chemical parameters and community structure of macroalgae. Physico-chemical parameters observed are the essential parameters for the livelihood of macroaelgae ecosystem such as temperature, salinity, water clarity, current, pH, dissolved oxygen, phosphate and nitrate. The result showed that water quality in these waters still within the water quality standard threshold for marine biota (KMLH, 2004) and still in the optimum range for growth of macroalgae. 21 species of macroalgae were found with varying density between 0.25 ind./m2-1.13 types ind./m2. The highest biomass were found in Gracilaria salocornia, which reached 1132.00 g/m2. Macroalgae diversity index (H ') were average, ranged from 2.716 to 2.978 and dominance index (D) were categorized as low, ranged from 0.0539 to 0.0697, while the index of uniformity (e) were ranged from 0.9754 to 0.9796, categorized as evenly distributed or stable. Keywords: Water quality, macroalgae, Community Structure.   ABSTRAK Studi tentang kualitas air dan komunitas makroalga di perairan pantai Jikumerasa, Pulau Buru, Maluku telah dilakukan pada bulan Juni 2014. Penelitian ini bertujuan untuk mengetahui kualitas perairan ditinjau dari parameter fisika-kimia dan struktur komunitas makroalga.  Parameter fisika-kimia yang diamati merupakan parameter utama bagi ekosistem makroalga diantaranya suhu, salinitas, kecerahan air, arus, pH, oksigen terlarut, fosfat dan nitrat.  Hasilnya menunjukkan bawa kualitas air di perairan ini masih dalam ambang batas baku mutu air untuk biota laut (KMLH, 2004) dan masih berada pada kisaran optimal untuk pertumbuhan makroalga.  Makroalga yang ditemukan sebanyak 21 jenis dengan kepadatan jenis bervariasi antara 0,25 ind./m2-1,13 ind./m2. Biomassa tertinggi terdapat pada jenis Gracilaria salocornia mencapai 1132,00 g/m2. Indeks keanekaragaman makroalga cukup tinggi yakni (H’) 2,716-2,978 dikategorikan sedang dan indeks dominasi (D) 0,0539-0,0697 dikategorikan rendah sedangkan indeks keseragaman (e) 0,9754-0,9796 dikategorikan stabil atau merata. Keywords: Kualitas Perairan, Makroalga, Struktur Komunitas.   1 Proyek Penelitian Biota Laut di Perairan Jikumerasa, Pulau Buru, DIKTI 2014 2 Pusat Penelitian Laut Dalam Ambon-LIPI 3 UPT. Loka Konservasi Biota Laut Bitung-LIPI